Health Promotion Strategy On Increasing Public Knowledge Regarding Early Detection Of Tuberculosis At The Fransisco Borja Da Costa Fatuberliu State High School, Manufahi Regency - Chatarina Umbul Wahyuni; Jermano Pinto (CV. AFDIFAL MAJU BERKAH, 2026)
This study was conducted in the context of Fatuberliu District, Manufahi Regency, Timor Leste, as a rural area with limited health access, high unemployment rates, and a significant incidence of tuberculosis, necessitating effective health promotion strategies to improve early detection of TB among adolescents. The purpose of this study was to evaluate the effect of health education based on the Extension Program Unit on increasing public knowledge regarding early detection of tuberculosis at the Francisco Borja da Costa Filial Public High School. This study used a quantitative approach with a quasi-experimental one-group pretest-posttest design on 25 adolescent participants aged 17–25 years, with a knowledge questionnaire instrument that was tested for content validity and reliability, then analyzed using paired samples t-test and descriptive analysis. The results showed an increase in the average knowledge score from 45.40 in the pretest stage to 78.60 in the posttest, with a decrease in the proportion of respondents with less knowledge from 92.0% to 12.0% and an increase in the good category from 8.0% to 88.0%. This study concludes that structured and interactive health education in the school environment significantly improves adolescents' knowledge about early detection of tuberculosis, making it worthy of being adopted as a community health intervention model in remote areas with limited access to health facilities.